FORMULATION AND EVALUATION OF FAST DISSOLVING TABLETS OF AMOXICILLIN TRIHYDRATE USING SYNTHETIC SUPERDISINTEGRANTS - KAMAL SAROHA; GAUTAM KUMAR; YASH PAUL (International Journal of Pharma and Bio Sciences, 2013)
In present study, the fast dissolving tablets of Amoxicillin Trihydrate were prepared by direct compression technique using microcrystalline cellulose (MCC) as direct compressible diluents. Sodium starch glycolate (SSG) and croscarmillose sodium (CCS) used as synthetic superdisintegrants. The swelling indices of the superdisintegrants were also compared. Among both the superdisintegrants, croscarmillose sodium showed the highest swelling index. The blends showed satisfactory flow properties. Eight formulations were prepared using different concentrations of Superdisintegrants and were investigated for their effect on the disintegration time and dissolution rate of the tablets. Tablets were also evaluated for weight variation, hardness, thickness, friability and drug content. All the tablets exhibited acceptable pharmaco-technical properties. Tablets prepared with the blend of CCS (60mg) exhibited quicker disintegration. According to the present study, it was found that tablets of batch F8 (blend containing CCS 60mg) showed better disintegrating property as well as % drug release (99.78% within 25 min.) than the most widely used synthetic superdisintegrants like SSG in the formulations of FDTs.